Post-Brexit : enter the mini-Brexits - Kliem, Frederick (2021)
Great Britain and the European Union finally agreed upon their Trade and Cooperation Agreement. It was a long, arduous process. Although Brexit comes at a high social and political price, eventually, moderate Brexiteers got much of what they were looking for. What about the future?